Report on the Proposed Ethics and Religious Culture Program - The English Speaking Catholic Council (ESCC) (2006)
We affirm the positive objectives of this program, namely: 1) To incorporate ethics and religion into public education; 2) To foster students’ capacity to know and express their moral and religious convictions within a pluralistic context; 3) To develop the capacity for meaningful dialogue about diverse moral and religious convictions; 4) To anchor this program in the distinctive cultural and religious heritage of Quebec. However, we recommend some major revisions to the program. Five interrelated areas stand out for us.